Importance of learning styles in teaching and learning during the COVID-19 pandemic: A critical review of recent studies - Frank Angelo Pacala (Academy of Cognitive and Natural Sciences, 2024)
The COVID-19 pandemic has necessitated a shift toward online education, making it more critical than ever to understand the impact of learning styles on teaching and learning. This critical review examined recent studies on the topic and highlights the significance of catering to individual learning styles to optimize student performance in diverse educational settings. From all the articles, four main concepts emerged: implementing effective teaching strategies for diverse learners, identifying and using learning styles to cater to student's individual needs, supporting students with individualized needs during remote instruction, and evaluating and assessing student learning in an online environment. Schools and teachers could identify students' learning styles using various tools. They could also use these learning styles to fit their teaching strategies in the class and the assessments. Teachers used a variety of educational tools and artificial intelligence for individualized instruction. The review concluded that educators incorporated various teaching methods and technologies to accommodate students' learning preferences and foster meaningful engagement in virtual classrooms, particularly during these challenging times.